Predictors of occult lymph node metastasis in cutaneous head and neck melanoma - Jonathan S. Ni (KeAi Communications Co., Ltd., 2019)
Objective: To use the Surveillance, Epidemiology, and End Results (SEER) database to verify the findings of a recent National Cancer Database (NCDB) study that identified factors predicting occult nodal involvement in cutaneous head and neck melanoma (CHNM) while identifying additional predictors of occult nodal metastasis and comparing two distinct cancer databases. Methods: Cases of CHNM in the SEER database diagnosed between 2004 and 2014 were identified. Demographic information and oncologic data were obtained. Univariate and multivariate analysis were performed to identify factors associated with pathologic nodal positivity. Results: There were 34002 patients with CHNM identified. Within this population, 16232 were clinically node-negative, 1090 of which were found to be pathologically node-positive. On multivariate analysis, factors associated with an increased risk of occult nodal metastasis included increasing depth of invasion (stepwise increase in adjusted odds ratio [OR]), nodular histology (aOR: 1.47 [95% CI: 1.21–1.80]), ulceration (aOR: 1.74 [95% CI: 1.48–2.05]), and mitoses (aOR: 1.86 [95% CI: 1.36–2.54]). Factors associated with a decreased risk of occult nodal metastasis included female sex (aOR: 0.80 [0.67–0.94]) and desmoplastic histology (aOR: 0.37 [95% CI: 0.24–0.59]). Between the SEER database and the NCDB, factors associated with occult nodal involvement were similar except for nodular histology and female sex, which did not demonstrate significance in the NCDB. Conclusion: Regarding clinically node-negative CHNM, the SEER database and the NCDB have similarities in demographic information but differences in baseline population sizes and tumor characteristics that should be considered when comparing findings between the two databases. Level of evidence: 4. Keywords: Head and neck melanoma, Lymph node metastasis, Occult nodal metastasis, Sentinel lymph node biopsy